Assessment of powdery mildew (Blumeria graminis f. sp. hordei) resistance genes in Turkish barley varieties - Zeybek, Ahmet; Dere, Şahin; Gök, Gülay; Çallak, Asude; Akkaya, Mahinur (Phytoprotection, 2008)
Thirty-four Turkish barley (Hordeum vulgare) varieties were tested for the presence of resistance genes (R-genes) to powdery mildew (Blumeria graminis f. sp. hordei) using the “leaf segment test” with nine isolates of the fungus. The most commonly found R-gene was Mla8, while a combination of R-genes Mlg and Ml(CP) was found in three varieties (Tokak 157/37, Beysehir 98, Konevei 98). The gene Mlh was found in four varieties (Obruk 86, Anadolu 86, Çıldır 02, Özdemir 05), while no R-gene was found in three varieties (Hamidiye 85, Yesevi 93, Bülbül 89). No clear inferences could be made for the partly-resistant varieties Gemici 7243, Yea 793.12 and Akhisar 98 using the test isolates selected, which suggests the presence of still unidentified R-genes. Overall, 10 previously characterized R-genes for powdery mildew (Mla8, Ml(La), Mlg, Ml(CP), Mlh, Mlat, Mla1, Mlh, Mla7, Mlra) were present in Turkish barley varieties, along with some other(s) still to be identified.